2019
DOI: 10.1002/ajpa.23937
|View full text |Cite
|
Sign up to set email alerts
|

Population history of southern Italy during Greek colonization inferred from dental remains

Abstract: Objectives:We are testing competing scenarios regarding the population history of the ancient Greek colonization of southern Italy using dental phenotypic evidence. Materials and Methods:We collected dental metric and nonmetric trait data for 481 human skeletons from six archaeological sites along the Gulf of Taranto, dating to pre-colonial (900-700 BC) and post-colonial periods (700-200 BC). We are evaluating scenarios through an individual-level biodistance analysis using a three-pronged approach: (a) by ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Third, we used a phenotypic distance statistic for measuring between-population variation that is assuming complete independence among traits. Although it has been repeatedly shown that correlations among dental traits recorded on key teeth are low (8,9,14,15,44), even modest trait correlations may lead to overrepresented variation from traits that co-occur. Given the limitations of our study, the reportedx r utility estimates must be considered as minimum and not as exact estimates of the strength of correlation between neutral genetic and dental morphological variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, we used a phenotypic distance statistic for measuring between-population variation that is assuming complete independence among traits. Although it has been repeatedly shown that correlations among dental traits recorded on key teeth are low (8,9,14,15,44), even modest trait correlations may lead to overrepresented variation from traits that co-occur. Given the limitations of our study, the reportedx r utility estimates must be considered as minimum and not as exact estimates of the strength of correlation between neutral genetic and dental morphological variation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, trait frequencies are expected to be correlated with the level of trait expressivity within a population under a threshold model of quasicontinuous variation (57). Dental traits listed in the ASUDAS have little or no sexual dimorphism (14,15); therefore, it is a standard procedure to pool sexes (4,6,8,12). Population comparisons based on ASUDAS dental traits typically focus on key teeth (usually the most mesial member of a tooth district) because these are considered the most stable members in terms of development and evolution (15) and are largely independent from each other (8,9,14,15,44).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Punics, the other main shapers of the Iron Age Sicilian genetic make-up were the Greeks, who established colonies on the island (and South Italy) starting from the 8 th century BCE [39]. According to recent findings, the Greek colonization was a more gradual and peaceful process than that described by ancient historians, characterized by greater interaction and close cohabitation between newcomers and local people [45]. This is probably the reason why modern southern Italians display a varying amount of Greek genetic influence [39], which could be described as a "Mediterranean continuum".…”
Section: Iron Agementioning
confidence: 99%
“…Dental nonmetric traits are assumed to lack significant sexual dimorphism, have minimal influence from divergent selection, and have high heritability (Irish et al, 2020;Scott & Irish, 2013;Scott & Turner II, 1997;Turner II et al, 1991). The required methods to analyze and quantify dental morphology are also cost efficient, and since teeth are often found in the archaeological record and highly resilient to taphonomic processes (Hillson, 2005), they are a good alternative to reconstruct population biological affinities and human mobility on individual , local Turner II & Scott, 1977), regional (Irish et al, 2017;Rathmann et al, 2019;Sutter, 2009;Turner II, 1976), and global scales (Hanihara, 2008;Scott & Irish, 2017;Scott & Turner II, 1997;Sutter, 2005). A prolific example of the latter can be seen in studies discussing the peopling of the Americas (Greenberg et al, 1986;Huffman, 2014;Powell, 1995Powell, , 1997Powell & Neves, 1998;Scott, Schmitz, et al, 2018;Stojanowski et al, 2013;Stojanowski & Johnson, 2015;Sutter, 2005;Turner II & Scott, 2013).…”
mentioning
confidence: 99%